Constitutive hippocampal cholesterol loss underlies poor cognition in old rodents - Martín, Mauricio Gerardo (2014)
Fil: Martín, Mauricio Gerardo. Consejo Superior de Investigaciones Científicas. Centro de Biología Molecular Severo Ochoa; España.